A new species of Asplenium (Aspleniaceae) from northwest Fujian (China) based on molecular and morphological data - Chen, Shui-Fei; Zheng, Xiao; Ge, Xiao-Min; Han, Yu-Tong; Deng, Meng-Dan; Ding, Hui; Xu, Ke-Wang (Phytotaxa, 2025)
A new species, Asplenium latipinnulum H. Ding & K.W. Xu, is described from the Wuyishan National Nature Reserve in Fujian, China. Our phylogenetic analyses of six chloroplast loci indicate that this new species is most closely related to A. indicum Sledge, A. planicaule Wall. ex Mett., and A. yoshinagae Makino. They are mainly distributed in eastern and southern Asia. Morphologically, A. latipinnulum is distinguished from A. indicum, A. planicaule, and A. yoshinagae primarily by its 2-pinnate laminae. Additionally, the combination of bright brown rhizome scales, larger fronds with laminae measuring up to 40 cm in length and 18 cm in width, and dark brown to black abaxial stipes and rachises further differentiates the new species from superficially similar species within the A. austrochinense subclade.